Anglerfish Discarding Behavior in Spanish North Atlantic Coast Fisheries - Santos-Blanco, Juan; Salinas-Aguilera, Miren Itxaso; Pérez-Contreras, María Nélida (2012)
Discard behavior in Spanish north Atlantic (ICES VIIIc,IXa) coastal fisheries concerning anglerfish species (Black anglerfish, L. budegassa and White anglerfish, Lophius piscatorius) is revisited herein. Results indicate that Angler discards basically depends on their length size. Year effect significantly conditioned discard behavior after 2000. Species differences in discard patterns were found also significant, being the less valuable white angler discarded at larger lengths than the black species. Diferent onboard sorting behavior indicates that fishers recognize angler species even at low length sizes, conditioning the degree of adoption of the assessment tools with regards to their relative market value.